Strategic Analysis Of Business Mode Canvas At Es Teh Indonesia Kebun Pramuka Banjarmasin - Izzati, Ridha Nur; Wulandari, Dyah Sri; Analisa, Analisa (Pasundan Social Science Development, 2025)
The Business Model Canvas is a business model of a logical description of how an organization creates, delivers and captures value. There are nine basic building blocks of the business model canvas that show how to think about how the company is more productive. The nine blocks are customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures. After that, it is divided into two sides, the left side as logic and the right side as creativity. Objective: This study aims to analyze the Business Model Canvas strategy and swot analysis, to be used in the promotion of coffee "Esteh Indonesia" Kebun Pramuka Banjarmasin. This research uses qualitative methods. Result , Based on the research, the results of several business model canvas from nine elements are quite fulfilled and connected with SWOT analysis to evaluate this business. Based on the results of the research that has been done, the Business Model Canvas strategy is used to analyze in SWOT, usefel in developing this business